Pengelolaan Barang Milik Daerah ditinjau dari Proses Perencanaan, Pelaksanaan dan Pengawasan - Wahyu Sidik Purnomo (Universitas Islam Kadiri, 2020)
Management of Regional Property in the Kediri Regency Government still faces many obstacles, especially in administering regional property, so that optimality in the management of regional property has not been achieved. As for the purpose of this study to determine the effect of the planning, implementation and supervision of goods management owned by region in the Kediri Regency Government. The type of research used is quantitative descriptive wherein this type of design is used with the consideration that researches uses in real life contexts. The population in this research was the regional goods manager, namely The Goods Manegment Staff an the Official Management of Goods Management at 66 SKPD in Kediri Regency Government. The conclusion in this research are planning, implementation and supervision affect the management of regional property both simultaneosly and partially.